2021
DOI: 10.5114/hm.2023.107247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic High Intensity Interval Training on glycosylated haemoglobin in people with type 2 diabetes: a meta-analysis

Abstract: type 2 diabetes is a chronic disease with an increasing prevalence all over the world. the treatment includes an integral intervention with medical treatment, healthy diet, and regular exercise. High Intensity Interval training has been recently proposed as part of this treatment to improve glycaemic control. the aim of this meta-analysis is to determine the effect of High Intensity Interval training on glycosylated haemoglobin in people with type 2 diabetes during at least 12 weeks of intervention. the search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Glycosylated haemoglobin (HbA1c) is a biochemical measurement used to monitor diabetes. Diabetes patients that practice sedentary condition (inactive in physical activities) will increase the HbA1c and it could worsen the glycaemic control and diabetes condition [11], [12]. A normal HbA1c level for people who does not diagnose with diabetes is below than 5.7%, while when the levels are between 5.7% to 6.4%, they are called pre-diabetes, and levels higher than 6.4% indicates diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycosylated haemoglobin (HbA1c) is a biochemical measurement used to monitor diabetes. Diabetes patients that practice sedentary condition (inactive in physical activities) will increase the HbA1c and it could worsen the glycaemic control and diabetes condition [11], [12]. A normal HbA1c level for people who does not diagnose with diabetes is below than 5.7%, while when the levels are between 5.7% to 6.4%, they are called pre-diabetes, and levels higher than 6.4% indicates diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…A research has been found that high intensity interval training (HIIT) has a positive impact on the condition of diabetes where HIIT could improve the glycaemic control or reduce the HbA1c [11]. A recent meta-analysis study shows that HIIT and moderate intensity have reduced the HbA1c of the diabetes participants, compared to low intensity training, and control training [13].…”
Section: Introductionmentioning
confidence: 99%